Energy from biogas, wood gas and photovoltaic system in rural properties - Silveira, José Luz; Abreu, Leila Rosa Carballo; Montesino, Francisco Márquez; Junior, Ederaldo Godoy; Zanzi, Rolando (Revista Ciências Exatas, 2008)
The present work support technical and economical bases for the implantation of hybrid system, for rural properties. The system consists in anaerobic biodisgester, gasifier of wood, engine, cogeneration system, and a photovoltaic system, for to guarantee auto sufficiency energetic in rural property. The proposal is to obtain biogas from the anaerobic treatment of excrements of 80 bovine cattle head, gas producer from wood residues, and approach solar incidence. The electric potency required in a property can be of 5, 8 kW in order to convert in auto sufficient the rural property. A production of biogas is insufficient for to satisfy energy in this community, for this reason is convenient associate one photovoltaic system, therefore during day, solar energy supply the energetic demand, at night works with biogas, Which was stored during the day, and gas producer. Technical and economical aspects associate with this system permits implantations in localities where the electric energy is impossible, the social contribution can be due the photovoltaic energy being utilized in educational programs. This system becomes an important environmental contribution.